Comparative analysis of COVID-19 incidence and neutralizing antibody response after primary COVID-19 vaccination and heterologous booster doses in adolescents vs. adults: the Indonesian experience - Karyanti, Mulya Rahma; Satari, Hindra Irawan; Munasir, Zakiudin; Hadinegoro, Sri Rezeki; Widyahening, Indah Suci; Sasmono, R Tedjo (Indonesian Pediatric Society, 2025)
Background The Indonesian COVID-19 immunization program has provided primary doses of a COVID-19 vaccine to adolescents and adults, while booster doses were given to adults only. Evaluation of this program is crucial to determine if boosters should be recommended for adolescents. Objective To compare COVID-19 incidence and SARS-CoV-2 IgG neutralizing antibody levels after COVID-19 vaccination in adolescents given a primary dose vs. adults given a primary dose and a booster. Methods: In this cross-sectional study, participants were given questionnaires on their COVID-19 history and evaluated for SARS-CoV-2 IgG neutralizing antibody titers. We included healthy individuals aged 12 years or older who resided in Jakarta and consented to participate, had received primary COVID-19 vaccine doses, and for adults, booster doses. Participants were stratified into two age groups, adolescents (12-17 years) and adults (18 years and above). We compared the incidence of COVID-19 and SARS-CoV-2 antibody titers between the two age groups. Results Out of 419 participants who met the inclusion criteria, 159 had blood specimens drawn for measurement of SARS-CoV-2 antibody titers. Before the widespread administration of the vaccine, the incidence of COVID-19 in was 4.9% in adolescents vs. 10.2% in adults (P=0.036). After widespread vaccination, the incidence of COVID-19 remained lower in adolescents than in adults (2.2% vs. 8.8%, respectively; P=0.005). The median SARS-CoV-2 antibody titer post-COVID-19 vaccination was 97.85 (range 46.46-98.23) U/mL in adults vs. 96.78 (range 22.08-98.23) U/mL in adolescents (P<0.05). Conclusion While the incidence of COVID-19 was significantly lower in vaccinated adolescents than in vaccinated adults, titers of SARS-CoV-2 IgG neutralizing antibody in adolescents were significantly lower compared to that of adults.